1999
DOI: 10.1121/1.426504
|View full text |Cite
|
Sign up to set email alerts
|

Preventative medical limits for chronic traffic noise exposure

Abstract: Because of an expert’s report on the medical effects of noise on healthy adults, permissible values for mainly traffic noise have been estimated by the standard of knowledge. If the permissible values are exceeded, then preventative medical action is necessary. Below this value the probability of noise-induced health hazards is essentially zero. The effect due to noise as a health hazard is, besides the mechanical damage of the inner ear, a psycho-physiological deregulation which can be either indirectly due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
13
0
7
Order By: Relevance
“…Findings of the study showed that traffic noise has negative impacts on human health, as is reported by others (Mato and Mufuruki, 1999;Georgiadou et al, 2004). Maschke (2001) and Babisch et al (1999) have pointed out some effects of the noise over urban inhabitants: irritability, insomnia, difficulty to concentrate and headaches. It has been observed that everybody within the group "Annoyed by Urban Noise" had declared that they felt at least one of the effects related above.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of the study showed that traffic noise has negative impacts on human health, as is reported by others (Mato and Mufuruki, 1999;Georgiadou et al, 2004). Maschke (2001) and Babisch et al (1999) have pointed out some effects of the noise over urban inhabitants: irritability, insomnia, difficulty to concentrate and headaches. It has been observed that everybody within the group "Annoyed by Urban Noise" had declared that they felt at least one of the effects related above.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 O nível equivalente de ruído (L eq ) de 65 dB(A) é considerado o limiar de conforto acústico para a medicina preventiva. A exposição contínua à valores acima desse limite pode causar distúrbios psico-fisiológicos diversos, 8 independente da idade, tais como distúrbios no sono, diminuição da performance laboral, hipertensão, agravamento de doenças cardiovasculares. 2,11 Os efeitos orgânicos podem ser observados quantitativamente por meio de exames laboratoriais, como a audiometria.…”
Section: Introductionunclassified
“…This process of occupation, in most cases, takes place in a disordered fashion, i.e., without adequate urban planning, causing an excessive increase in the number of sound sources (Zannin et al 2001;Maschke 1999). Several sectors of the society are affected by TN, and schools are one of the spots most sensitive to this type of environmental pollution (Zannin and Zwirtes 2009;Zannin and Marcon 2007;Krüger and Zannin 2004).…”
Section: Introductionmentioning
confidence: 99%